Case report: persistent fever after SARS-CoV-2 infection Fallbericht: Persistierendes Fieber nach SARS-CoV-2-Infektion - Kliem, Thorsten; Strobel, Deike; Heinke, Fabian; Pavel, Marianne Ellen; Neurath, Markus; Neufert, Clemens (Internist, 2022)
A 44-year-old man had persistent fever following a severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) infection. Because of progressive sinus tachycardia, thyroid hormones were measured which showed hyperthyroidism. Thyroid sonography revealed enlargement of the thyroid gland with hypoechoic areas with blurred margins. We diagnosed subacute granulomatous thyroiditis associated with SARS-CoV‑2 infection and initiated therapy with prednisolone. This therapy resulted in rapid improvement of the patient’s clinical condition and complete remission after three months.
CRIS-Team Scopus Importer:2022-04-01
Keywords: COVID-19; De Quervain’s thyroiditis; Diagnostic ultrasound; Subacute granulomatous thyroiditis; Tachycardia

Impact of Cytokine Inhibitor Therapy on the Prevalence, Seroconversion Rate, and Longevity of the Humoral Immune Response Against SARS-CoV-2 in an Unvaccinated Cohort - Simon, David; Tascilar, Koray; Kleyer, Arnd; Fagni, Filippo; Krönke, Gerhard; Meder, Christine; Dietrich, Peter; Orlemann, Till; Kliem, Thorsten; Moessner, Johanna; Liphardt, Anna-Maria; Schönau, Verena; et al. (Arthritis and Rheumatology, 2022)
Objective To investigate the impact of biologic disease-modifying antirheumatic drug (bDMARD) treatment on the prevalence, seroconversion rate, and longevity of the humoral immune response against SARS-CoV-2 in patients with immune-mediated inflammatory diseases (IMIDs). Methods Anti-SARS-CoV-2 IgG antibodies were measured in a prospective cohort of health care professional controls and non-health care controls and IMID patients receiving no treatment or receiving treatment with conventional or biologic DMARDs during the first and second COVID-19 waves. Regression models adjusting for age, sex, sampling time, and exposure risk behavior were used to calculate relative risks (RRs) of seropositivity. Seroconversion rates were assessed in participants with polymerase chain reaction (PCR)-positive SARS-CoV-2 infection. Antibody response longevity was evaluated by reassessing participants who tested positive during the first wave. Results In this study, 4,508 participants (2,869 IMID patients and 1,639 controls) were analyzed. The unadjusted RR (0.44 [95% confidence interval (95% CI) 0.31-0.62]) and adjusted RR (0.50 [95% CI 0.34-0.73]) for SARS-CoV-2 IgG antibodies were significantly lower in IMID patients treated with bDMARDs compared to non-health care controls (P < 0.001), primarily driven by treatment with tumor necrosis factor inhibitors, interleukin-17 (IL-17) inhibitors, and IL-23 inhibitors. Adjusted RRs for untreated IMID patients (1.12 [95% CI 0.75-1.67]) and IMID patients receiving conventional synthetic DMARDs (0.70 [95% CI 0.45-1.08]) were not significantly different from non-health care controls. Lack of seroconversion in PCR-positive participants was more common among bDMARD-treated patients (38.7%) than in non-health care controls (16%). Overall, 44% of positive participants lost SARS-CoV-2 antibodies by follow-up, with higher rates in IMID patients treated with bDMARDs (RR 2.86 [95% CI 1.43-5.74]). Conclusion IMID patients treated with bDMARDs have a lower prevalence of SARS-CoV-2 antibodies, seroconvert less frequently after SARS-CoV-2 infection, and may exhibit a reduced longevity of their humoral immune response.
CRIS-Team WoS Importer:2022-04-08

LONG-TERM HUMORAL RESPONSE TO SARS-COV-2 VACCINATION IN PATIENTS WITH IMMUNE-MEDIATED INFLAMMATORY DISEASE - Tascilar, Koray; Simon, David; Kleyer, Arnd; Fagni, Filippo; Krönke, Gerhard; Meder, Christine; Dietrich, Peter; Orlemann, Till; Kliem, Thorsten; Moessner, J.; Liphardt, Anna-Maria; Schönau, Verena; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04